2023
DOI: 10.3389/fonc.2022.1042459
|View full text |Cite
|
Sign up to set email alerts
|

Rare primary bladder mucosa-associated lymphoid tissue lymphoma: A case report and review of literature

Abstract: Primary bladder mucosa-associated lymphoid tissue (MALT) lymphoma is an extremely rare bladder tumor. Only scarce reports have been reported. We hereby report a case of an 81-year-old female patient with bladder tumor presenting with frequent urination and dysuria, whose pelvic magnetic resonance imaging (MRI) considered bladder cancer. She underwent transurethral resection of the bladder tumor (TURBT), and histopathology confirmed the mass to be bladder MALT lymphoma. The patient refused further treatment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Al‐Obaidy et al further characterized examples of this entity in multiple studies and labeled it as PRNRP, 2 which is the currently adopted nomenclature for this entity. To date, more than 100 PRNRP cases have been reported, and to the best of our knowledge, there are no known cases with documented disease progression or metastasis 2–4,13–18 . Similar to the previous reports, we have also found that PRNRPs had significantly smaller tumor size, lower WHO/ISUP grade, and lower stage than ePRCCs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Al‐Obaidy et al further characterized examples of this entity in multiple studies and labeled it as PRNRP, 2 which is the currently adopted nomenclature for this entity. To date, more than 100 PRNRP cases have been reported, and to the best of our knowledge, there are no known cases with documented disease progression or metastasis 2–4,13–18 . Similar to the previous reports, we have also found that PRNRPs had significantly smaller tumor size, lower WHO/ISUP grade, and lower stage than ePRCCs.…”
Section: Discussionsupporting
confidence: 89%
“…The evidence gathered to date indicates that PRNRP has an indolent clinical course. Most of the reported cases are pT1a stage and often they are smaller in size, below the papillary adenoma size cutoff of 1.5 cm 3,4 . To our knowledge, there are no reported cases of disease progression, documented as recurrence or metastasis 2,3 .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The International Lymphoma Radiation Oncology Group (ILROG) suggests for indolent extranodal lymphomas a dose range of 20-30 Gy [15]. In the literature, the dose received by primary bladder MALT lymphoma ranged from 24 to 36 Gy [4,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%